Fabrication, testing and performance enhancement of a small scale tidal current turbine / Ng Kai Wern - Ng, Kai Wern (2018)
The working concept of a horizontal-axis tidal current turbine (HATCT) is similar to that of wind turbines. The technology used in wind turbine can be readily transferred to tidal current turbines. This is exactly what is going on at the moment in HATCTs industry. Malaysia is a country that can benefit from tidal current turbine, especially in the Straits of Malacca. The current flow in the Straits of Malacca varies from 0.5m/s to 1.5m/s, and reaches 2.0m/s or above at some localities. Considering the benchmark of economic power generation for tidal current turbines to be around 1.5m/s, harnessing tidal current energy looks promising for Malaysia. However, to-date, no study on creating a workable turbine has been reported for Malaysia. Therefore, it is the aim of the current research to study workability and performance of an operational tidal current turbine for Malaysia. The testing and modification of turbine were done with the sponsor and help of Laison Engineering Sdn. Bhd. A 800mm five-bladed turbine was tested at Pangkor Island. The original setting of the prototype turbine was not able to produce steady power output. But after a few modifications on the generator and shaft, a power coefficient of approximately 0.32 was achieved with current velocity of 0.25m/s. Besides the fabrication and testing of the turbine, an innovative method to improve the efficiency of tidal current turbine has also been studied. The innovative method was the use of hydrophobic antifouling paint. Antifouling paint is an important protection measure for tidal current turbine to against marine bio-fouling. Marine bio-fouling has deteriorating effects on the performance of tidal current turbine once they are attached on the turbine blades. Hydrophobic anti-fouling paint is one of the common types of anti-fouling paint that is used. Interestingly, its hydrophobicity has the ability to reduce friction drag over a surface. As such, hydrophobic anti-fouling can potentially provide performance enhancement for a tidal current turbine, meanwhile protects turbine blades from marine bio-fouling. Two commercial hydrophobic antifouling coatings, Biocyl and a normal hydrophobic coating, Always Dry were used. Experiment has been conducted to understand the effects of hydrophobic coating on hydrofoils and a 350mm diameter three-bladed turbine. It was found that both Biocyl and Always Dry lower the drag coefficient of NACA 63418 by an average of 3% and 3.5%. Biocyl has improved the revolution per minute of the turbine by an average of 1.3%, whereas Always Dry has improved the revolution per minute of the turbine by an average of 2.5%. Last but not least, two commercial antifouling paints, namely Bioycl and Palccoat, have been tested to understand their ability to protect tidal current turbine from marine bio-fouling activities in Pangkor Island. The field test results show that with these anti-fouling paints, the development of thin film on turbine blade can be postponed to 3~4weeks. Up to this stage, the thin film can still be cleaned. However, when barnacles started to grow on the blade, it is difficult to remove the barnacle by simple cleaning.